The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.hrtlng.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

High incidence and mortality of pneumothorax in critically Ill patients with COVID-19

Abstract: Highlights Pneumothorax may be a frequent and fatal complication in critically ill patients with COVID-19. Pneumothorax was likely to occur 2 weeks after the beginning of dyspnea in senile male patients. Mechanical ventilation, recruitment maneuver, forced inhalation, severely coughing, and changes of lung structure and function, contribute to the occurrence of pneumothorax. Lung recruitment maneuver should be cautiously considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(121 citation statements)
references
References 22 publications
8
94
1
2
Order By: Relevance
“…When taking into account critically ill COVID-19 patients, 23.8% (5/21) developed pneumothoraces indicating greater disease severity with mortality rates of 80.0% among those diagnosed. 19 These findings demonstrate that COVID-19 disease severity likely plays a vital role in explaining the high incidence of pneumothorax reported, consistent with greater IMV requirements and poor mortality rates observed.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…When taking into account critically ill COVID-19 patients, 23.8% (5/21) developed pneumothoraces indicating greater disease severity with mortality rates of 80.0% among those diagnosed. 19 These findings demonstrate that COVID-19 disease severity likely plays a vital role in explaining the high incidence of pneumothorax reported, consistent with greater IMV requirements and poor mortality rates observed.…”
Section: Discussionsupporting
confidence: 71%
“… 2 , 17 , 18 Among the two cross-sectional studies by Wang et al and Zantah et al, quality scores of six were reported. 19 , 20 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations